Shear behaviour of RC deep beams retrofitted with externally bonded GFRP fabrics: Experimental and numerical study. (December 2022) - Dutta, Baisali; Kumari, Archana; Nayak, Amar N.
Abstract: The structural behaviour of reinforced concrete (RC) deep beams strengthened in shear by externally bonded (EB) glass fibre reinforced polymer (GFRP) fabrics are investigated employing both experiment and finite element (FE) analysis using commercial software. Four RC deep beams of 1000 mm length, 120 mm width and 420 mm depth are prepared. One un-retrofitted and other three beams retrofitted with U-wrapping of GFRP fabrics along the shear spans are tested under two-point loading to obtain the various structural responses. Thereafter, the FE model is validated by comparing its structural responses with those of the experiment. From both investigations, it is found that there is a significant enhancement in structural responses, such as load-carrying capacity, deflection, shear capacity, stiffness and energy absorption capacity due to the retrofitting of beams. Then, a comparison of the shear strengths of the experiment, FE model and existing design models is made to check the efficiency of the present FE model. Finally, a numerical study is conducted to examine the influence of various wrapping patterns of GFRP fabrics on the structural performance of the retrofitted beams. From this study, it is found that the wrapping pattern influences the structural performance of the beam remarkably.